2019
DOI: 10.1186/s12879-019-4464-7
|View full text |Cite
|
Sign up to set email alerts
|

Rubella transmission and the risk of congenital rubella syndrome in Liberia: a need to introduce rubella-containing vaccine in the routine immunization program

Abstract: Background: Rubella is an RNA virus in the genus Rubivirus within the Matonaviridae family. Rubella remains a leading vaccine-preventable cause of birth defects. Most African countries including Liberia do not currently provide rubella-containing vaccine (RCV) in their immunization program. We analyzed the existing surveillance data to describe rubella cases and identify the at-risk population. Methods: We conducted a retrospective descriptive statistics on the suspected-measles case-based surveillance data th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Rubella cases identified in the context of measles surveillance between 2007 and 2014 (Farra et al, 2016), but also in the present study looking at 2015 and 2016 data showed an annual seasonal pattern, with peak incidences during the dry season between January and March. An increased incidence of rubella during the dry season was documented in basically all parts of Africa (Chimhuya et al, 2015, Getahun et al, 2016, Kadjo et al, 2018, Nimpa Mengouo et al, 2017, Omoleke and Udenenwu, 2016, Woyessa et al, 2019 and as suggested in a study done in Beijing is probably associated with meteorological variables, such as temperature and relative humidity (Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 81%
“…Rubella cases identified in the context of measles surveillance between 2007 and 2014 (Farra et al, 2016), but also in the present study looking at 2015 and 2016 data showed an annual seasonal pattern, with peak incidences during the dry season between January and March. An increased incidence of rubella during the dry season was documented in basically all parts of Africa (Chimhuya et al, 2015, Getahun et al, 2016, Kadjo et al, 2018, Nimpa Mengouo et al, 2017, Omoleke and Udenenwu, 2016, Woyessa et al, 2019 and as suggested in a study done in Beijing is probably associated with meteorological variables, such as temperature and relative humidity (Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 81%
“…Transmission usually occurs through respiratory droplets but can also occur to the fetus through placenta. Vertical transmission of rubella is higher in the first weeks of gestation, leading to miscarriage, stillbirth, or a chronic injury of several organs in the fetus, well-known as Congenital rubella syndrome (CRS), with the classical fetal Gregg's triad of congenital cataracts, deafness, and cardiac defects [ 88 ]. Mechanisms of fetal damage …”
Section: Rubella Virusmentioning
confidence: 99%
“…It is an RNA virus that belongs to the Rubivirus genus and Matonavirida family. [1][2][3][4] It is an infectious disease transmitted through respiratory droplets from person to person or through placenta from mother to her fetus. [3][4][5][6] The average incubation period is 14 days and a range of 12-23 days.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] It is an infectious disease transmitted through respiratory droplets from person to person or through placenta from mother to her fetus. [3][4][5][6] The average incubation period is 14 days and a range of 12-23 days. The first symptom is a maculopapular rash, which appears on the face and then extends to the body surface, lasting almost three days.…”
Section: Introductionmentioning
confidence: 99%